PENGARUH MODAL KERJA DAN JENIS BARANG DAGANGAN TERHADAP PENDAPATAN TOKO KELONTONG MADURA DI KECAMATAN JAMBANGAN KOTA SURABAYA - Rifdatul Hanifah; Joko Priyono (Nirta Learning Centre, 2025)
This study analyzes the influence of working capital and types of merchandise on the income of Madurese grocery store owners in Jambangan District, Surabaya. Using a quantitative method with a survey of 60 respondents, the data were analyzed using multiple linear regression, including the t-test, F-test, and coefficient of determination (R²). The t-test results show that working capital has a positive and significant effect on income, while the types of merchandise do not have a significant effect. Meanwhile, the F-test confirms that both variables simultaneously have a significant influence on income. The R² value of 21.7% indicates that the model explains only a small portion of income variation. The study recommends optimizing the use of working capital and adjusting merchandise types according to consumer needs to improve income and business competitiveness.